Innovation and Business Performance in Rural and Peripheral Areas of Greece - Alexandra Goudi; Dimitris Skuras; Kyriaki Tsegenidi (European Regional Science Association (ERSA), 2003)
The present work explores the extent and patterns of innovation in two mountainous areas of Greece and its effect on business performance. Innovative activity is categorized in fives classes of product and market innovation. Both areas are characterized by extreme rurality and peripherality but the one is more accessible by the market of two urban agglomerations while the other one is very remote. Empirical evidence are drawn from a survey of 160 enterprises in the manufacturing and service sectors. Product and market innovation is facilitated by the operation of various types of business networks and influenced by a range of entrepreneurial and enterprise specific characteristics. In turn, innovative activity has an impact on conventional measures of business performance. Policy implications for a territorially specific business innovation support strategy are drawn.
Keywords: 330